Application of Naive Bayes and Forward Chaining Methods in a Web-Based Expert System for Stunting Diagnosis in Toddlers - Fadilah, Ayu; Amanda Putri, Raissa (Politeknik Negeri Batam, 2025)
The high rate of stunting in toddlers shows the need for accurate early diagnosis to prevent long-term impacts on children's growth and development. One of the main obstacles to early diagnosis is parents' lack of knowledge about the early symptoms of stunting, so treatment is often delayed. To overcome this problem, a web-based expert system was developed that applies the Naïve Bayes and Forward Chaining methods in diagnosing stunting in toddlers. The Naïve Bayes method is used to calculate the possibility of stunting based on the symptoms experienced by toddlers. This method is a probability-based algorithm that is used to classify the possibility of a condition based on existing symptoms. The process begins by calculating the probability of each symptom of stunting disease based on historical data that has been collected from experts. Then, using Bayes' Theorem, the system calculates the greatest probability of a disease based on the symptoms selected by the user. The final output is the diagnosis that has the highest probability, along with the recommended solution. Meanwhile, Forward Chaining is used to trace the rules that lead to a diagnosis conclusion. The Naïve Bayes method focuses more on calculating probabilities to determine a diagnosis with a certain level of confidence, while the Forward Chaining method works by matching rules to obtain conclusions based on the facts provided. The combination of these two methods allows the expert system to make a more accurate diagnosis by considering the probabilities and rules set by the expert. The web-based system built using these two methods aims to help parents detect stunting in toddlers early, so they can immediately take appropriate preventive or treatment steps. The results of the research show that it is found that the symptoms experienced by children are likely to be diagnosed as Not Stunting with the highest value of 0.5192 or around 51.9% with the solution being that children who do not experience stunting show growth and development appropriate to their age. The system developed is able to provide diagnoses in accordance with expert evaluations, so that it can be used as a tool to assist parents in providing.